Incidencia del uso de software educativo en el proceso de enseñanza aprendizaje de factorización en el primer año de bachillerato especialidad informática de la sección nocturna de la Unidad Educativa Kleber Franco Cruz de la ciudad de Machala provincia de El Oro del periodo lectivo 2012-2013. - Pérez Molina, Jose Luis (2013)
Being this a powerful tool to arrive with motivation and interaction to the construction of the student's knowledge with the use of a techno-educational tool as it is the educational software of factorization and to give to the teachers the skills and the knowledge of the importance of using software Educational process in the teaching-learning process so as not to fall into the same traditional learning strategies that we know.